2015
DOI: 10.1007/978-3-319-16522-6_3
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Relevant to Cognition-Enhancing Drug Targets

Abstract: Aging is generally associated with a certain cognitive decline. However, individual differences exist. While age-related memory deficits can be observed in humans and rodents in the absence of pathological conditions, some individuals maintain intact cognitive functions up to an advanced age. The mechanisms underlying learning and memory processes involve the recruitment of multiple signaling pathways and gene expression, leading to adaptative neuronal plasticity and long-lasting changes in brain circuitry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 396 publications
(395 reference statements)
0
15
0
1
Order By: Relevance
“…One possible reason is that calcium chloride condenses nascent plasmid DNA to form stable and small nanoparticles with 100–140 nm in diameter, leading to the enhancement of gene expression [ 48 ]. Another possible reason is that calcium ion may activate transcription factors to facilitate gene expression through its downstream signaling effectors; for instance, calcium/calmodulin-dependent protein kinase II (CaMKII), protein kinase C (PKC), and cAMP response element-binding protein (CREB) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason is that calcium chloride condenses nascent plasmid DNA to form stable and small nanoparticles with 100–140 nm in diameter, leading to the enhancement of gene expression [ 48 ]. Another possible reason is that calcium ion may activate transcription factors to facilitate gene expression through its downstream signaling effectors; for instance, calcium/calmodulin-dependent protein kinase II (CaMKII), protein kinase C (PKC), and cAMP response element-binding protein (CREB) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…ERK activation has also been shown to be involved in learning of various hippocampus-dependent tasks (Menard et al, 2015; Peng et al, 2010; Xia and Storm, 2012). A previous study indicated that training in novel object recognition or in fear conditioning resulted in SCOP degradation and ERK activation in hippocampus 5 min after training (Shimizu et al, 2007).…”
mentioning
confidence: 99%
“…As such, defective IRS-1 dependent insulin signaling in the hippocampus has been associated with severe cognitive deterioration [15]. Interestingly, hippocampal expression of mTOR, a protein kinase involved in the insulin signaling pathway [16], was prominently enhanced by (d-Ser 2 ) Oxm[Lys 38 -γ-glu-PAL] treatment. These observations suggest that the improvement of peripheral insulin sensitivity noted with (d-Ser 2 )Oxm[Lys 38 -γ-glu-PAL] also extends to its central actions.…”
Section: Discussionmentioning
confidence: 99%